Improvement properties of laser cladding Ni45-Cr3C2 coatings by adding B4C and V - Yingpeng, Liu; Yunlong, Liang; Hanguang, Fu (Materials science and technology, 2023)
By adding B 4 C and vanadium to Ni45-Cr 3 C 2 powder in a moderate proportion, it is found that B 4 C will decompose into elements B and C during laser cladding, and the lattice constants of V and Cr elements are similar, which can form (Cr,V)B 2 phase with high hardness. According to the first principles calculation of the hardness of (CR 1-X V x )B, it can be seen that it shows a trend of increasing first and then decreasing. With the addition of B 4 C and vanadium, the mechanical properties of the composite coating increase. When the coating composition is Ni45-30Cr 3 C 2 -9B 4 C-15FeV50, the average microhardness, fracture toughness and wear resistance of the composite coating increase by 22.1%, 121.6% and 54.2%, respectively. Highlights Laser cladding composite coatings with different B 4 C and vanadium were prepared. V and Cr elements have similar lattice constants and can form a (Cr, V)B 2 phase with high hardness. The performance of the laser cladding composite coatings increased with the addition of B 4 C and vanadium.